Multimodal Analysis in Cigarette Advertisements - Santi Miharti; Fitrawati Fitrawati (Universitas Negeri Padang, 2022)
Abstract Multimodality is a term widely discussed by linguistics and semiotics. It means the combination of different semiotic modes, for example, language and music in a communicative artifact or event (Leeuwen, 2005). In this research, the researcher examines multimodal advertising for cigarette products. The cigarette products named is Djarum 76 and Sampoerna Kretek. This research is intended to 1) how semiotic systems in Djarum 76 and Sampoerna Kretek advertisements express meaning? 2) What is the generic structure placed in both advertisements? 3) What are the differences between semiotic systems in Djarum 76 and Sampoerna Kretek cigarette’s audiovisual advertisements? This research used the descriptive qualitative method. Analysis in this research using the semiotics approach focused on multimodal systems that include linguistic, visual, audio, and gestural aspects. Linguistic analysis using Systemic Functional Linguistic by (Halliday, 2004), visual, audio, and gestural analysis using Anstey and Bull (2010) theories, and Choeng (2004) formulation of generic structure potential for print advertisement. Keywords: Multimodality, advertisement, cigarette product, semiotic systems